Effect of hybrid natural fibre pineapple leaf fiber (PLAF) / carbon black fillers in styrene butadine rubber (SBR) composites on cure, physical and mechanical properties / Nabila Abu Osman - Osman, Nabila Abu (2020)
The properties of PALF is produced from pineapple leaf were revealed. There is urgent need for innovation for give better understanding and give potential for development nowadays. This research aims to study the effect of hybrid natural fibre pineapple leaf fiber (PLAF) / carbon black fillers in styrene butadiene rubber (SBR) composites on cure, physical and mechanical properties. The pineapple leaf is studies at Unit Ladang that use in this project. The effect on different phr (5,10,15,20) for treated and untreated PALF were determined. All effect of PALF were significantly influenced by all testing(except tensile testing and swelling index). The results of the study also suggested that need strategies to successfully on this project. The lack of management data and not knowing the quality of pineapple leaf is becoming growing concern. It is hope that the study can contribute to improvement on physical and mechanical of properties in this project.